Soil carbon loss with warming: New evidence from carbon‐degrading enzymes. (8th February 2020) - Chen, Ji; Elsgaard, Lars; van Groenigen, Kees Jan; Olesen, Jørgen E.; Liang, Zhi; Jiang, Yu; Lærke, Poul E.; Zhang, Yuefang; Luo, Yiqi; Hungate, Bruce A.; Sinsabaugh, Robert L.; Jørgensen, Uffe
Abstract: Climate warming affects soil carbon (C) dynamics, with possible serious consequences for soil C stocks and atmospheric CO2 concentrations. However, the mechanisms underlying changes in soil C storage are not well understood, hampering long‐term predictions of climate C‐feedbacks. The activity of the extracellular enzymes ligninase and cellulase can be used to track changes in the predominant C sources of soil microbes and can thus provide mechanistic insights into soil C loss pathways. Here we show, using meta‐analysis, that reductions in soil C stocks with warming are associated with increased ratios of ligninase to cellulase activity. Furthermore, whereas long‐term (≥5 years) warming reduced the soil recalcitrant C pool by 14%, short‐term warming had no significant effect. Together, these results suggest that warming stimulates microbial utilization of recalcitrant C pools, possibly exacerbating long‐term climate‐C feedbacks. Abstract : Our results, for the first time, identify progressive shifts from cellulase to ligninase as key drivers of soil C storage to long‐term experimental warming. These results provide new insights to reconcile the highly debated topic of the effects of climate warming on soil C storage, particularly for long‐term climate warming.